عروض مختصرة - فتحي حسن ملكاوي (International Institute of Islamic Thought, 2000)
• Hernands, De sots, the Mystery of capital: why capitalism Triumphs in the west and Fails Everywhere Else? London: Bantam press, 2000,244p. • البدوي، يوسف أحمد محمد، مقاصد الشريعة عند ابن تيمية. عمان: دار النفائس، 2000، 608 ص. • الميلاد، زكي. محنة المثقف الديني مع العصر. بيروت: دار الجديدة،2000 م، 144ص. • الشرقاوي، المالقي عائشة. البنوك الإسلامية: التجربة بين الفقه والقانون والتطبيق. الدار البيضاء: المركز الثقافي العربي، 2000م،704ص. • Chapra, M. umer. The future of economics: An Islamic perspective. Leicester, UK: the Islamic foundation. 2000, 446p. • Ramadan, Tariq. To be a European Muslim. Leicester, UK: the Islamic Foundation,1999,274p. • Abdelkader, Deina. Social Justice in Islam. Herndon, VA: International Institute of Islamic thought, 2000,216p. • Al Najjar, Abd al Majid. The viceregency of mon between Revelation and Reason: A Critique of the Dialectic of the Text, Reason, and Reality. Herndon, VA: International Institute of Islamic thought,2000,90p. • البنَّا رجب. الإسلام والغرب. القاهرة: دار المعارف، 2000. • Al-Ghazali, Muhammad. The socio-political thought of shah wali Allah. Islamabad: the International Institute of Islamic thought, 2001, 336p. • Armstrong, Karen. Islam: A Short History. London: Weidenfeld & Nicolson, 2000. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF  في اعلى يمين الصفحة.